2015
DOI: 10.25011/cim.v38i3.22707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pressure- and Volume-Controlled Ventilation in Laparoscopic Surgery: A Meta-analysis of Randomized Controlled Trial

Abstract: Purpose: Volume-controlled ventilation (VCV) has been the traditional mechanical ventilation mode in laparoscopic surgery. Pressure-controlled ventilation (PCV) has been used more frequently in recent years, especially for patients with complicated conditions; however, evidence on whether PCV is superior to VCV is still lacking. A meta-analysis was used to compare the effects of PCV and VCV on respiratory and hemodynamic parameters during laparoscopic surgery. Methods: PubMed and Embase were each searched fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
13
1
1
Order By: Relevance
“…Subgroup analysis showed the same results with the morbid obese patients. 18 Jiang et al in another meta-analysis compared PCV and VCV in 1643 patients in different positions (supine, lateral and prone)and conditions (one lung ventilation and laparoscopy) and showed that VCV is associated with decreased oxygenation index and increased alveolar-arterial oxygen difference. Subgroup analysis showed the same results during laparoscopy in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis showed the same results with the morbid obese patients. 18 Jiang et al in another meta-analysis compared PCV and VCV in 1643 patients in different positions (supine, lateral and prone)and conditions (one lung ventilation and laparoscopy) and showed that VCV is associated with decreased oxygenation index and increased alveolar-arterial oxygen difference. Subgroup analysis showed the same results during laparoscopy in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the eight enrolled RCTs, only three included laparoscopic pelvic surgeries which require steep Trendelenburg position that further compromises the respiratory mechanics altered after pneumoperitoneum. [ 8 ] Jiang et al . also recently conducted a meta-analysis of 27 trials with 1643 cases to compare PCV and VCV modes on different positions (supine, prone and lateral) and conditions (laparoscopic surgery, one lung ventilation, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis that compared PCV and VCV modes during laparoscopic surgery by Wang et al ( 2015 ) concluded that patients had PCV mode had lower P-peak and resistance accompanying higher compliance and P-mean levels. Although with subgroup analysis revealed the same results including morbid obese patients who underwent different kind of operations.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure-controlled ventilation (PCV), with its high and decelerating inspiratory flow, has faster tidal volume delivery and different gas distribution. The same tidal volume setting, delivered by PCV versus VCV, may result in a lower peak airway pressure and reduced risk of barotrauma, but variable tidal and minute volume may be generated (Campbell and Davis 2002 ; Wang et al 2015 ; Jiang et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%